Geography and computational science. - Armstrong, Marc P. (Annals of the Association of American Geographers, 2000)
Part of a special section on millennial essays that draw from the past and look forward to the future of geography. The writer discusses the opportunities for geography that come with the combination of computational science and geographical modeling. He details the causes of computational complexity and focuses on the development of synergistic interactions between computational science and geography, with particular emphasis on the use of novel computer architectures that improve the performance of models and foster their application in an enlarged set of policy and scientific contexts. He also explains how emerging computational technologies will start to alter approaches to the development of geographical models. He concludes by describing how a type of advanced visualization called immersion is producing a need to rethink aspects of cartography.